Isolasi dan Karakterisasi Bakteri Asam Laktat pada Tempoyak sebagai Fermentasi Tradisional Khas Jambi - Tata Anggraini; Ardi Mustakim (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Tempoyak is a traditional fermented product derived from the flesh of durian fruit (Durio zibethinus) that has undergone a spontaneous fermentation process. This product is very popular in various regions in Indonesia, especially in Sumatra and Kalimantan, and is usually consumed as a cooking spice or side dish. The fermentation process primarily involves the activity of lactic acid bacteria (LAB), a group of microorganisms capable of converting acidic sugars into lactate. LAB plays an important role in forming the distinctive taste of tempoyak, lowering pH, inhibiting the growth of pathogenic microbes, and potentially providing health benefits for consumers. This study aims to isolate and characterize LAB from tempoyak using a microbiological approach. Tempoyak samples were taken from traditional markets, then isolated using MRS agar measurement media. Characterization was carried out through observation of colony morphology, Gram staining, and biochemical tests such as catalase and fermentation of various types of sugars (glucose, sucrose, and maltose). The isolation results showed that all isolates had the typical LAB characteristics, namely Gram-positive, catalase-negative, and rod- and coccus-shaped. The different sugar fermentation abilities indicate species diversity, with the suspected dominant genera being Lactobacillus, Streptococcus, Enterococcus, and Lactococcus. Furthermore, several isolates demonstrated antibacterial activity against Escherichia coli, indicating the potential use of LAB from tempoyak as a probiotic or natural preservative in the food industry. The decrease in pH from 6.2 to 3.6 during the fermentation process also confirmed the metabolic activity of LAB in acid-producing lactate. These findings open up opportunities for utilizing local LAB from tempoyak as functional agents in the development of safe, healthy, and economically valuable fermented food products. Thus, tempoyak not only has cultural value but also has significant scientific and commercial potential.